2020
DOI: 10.3906/sag-1908-114
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effects of caffeic acid phenethyl ester and ankaferd blood stopper on secondary wound healing of oral mucosal tissue

Abstract: Introduction The wound healing process consists of four highly connected and overlapping processes: haemostasis, inflammation, proliferation, and tissue remodelling [1]. These stages and their biophysiological functions take place in a specific sequence, at a particular time, and for a specific period at an optimal intensity [2]. Many factors can affect wound healing and interfere with one or more phases of the wound healing process, leading to incomplete tissue repair [3]. After periodontal surgery, both bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Although fibrosis formation was statistically similar in both groups, the group treated with ABS had a lower rate of fibrosis than the untreated control group. More dense new bone formation and less necrosis were reported in defects treated with ABS, possibly as a result of an increase in healing speed and a decrease in inflammation associated with the antioxidant activity of ABS components (18,32).…”
Section: Discussionmentioning
confidence: 95%
“…Although fibrosis formation was statistically similar in both groups, the group treated with ABS had a lower rate of fibrosis than the untreated control group. More dense new bone formation and less necrosis were reported in defects treated with ABS, possibly as a result of an increase in healing speed and a decrease in inflammation associated with the antioxidant activity of ABS components (18,32).…”
Section: Discussionmentioning
confidence: 95%
“…Experimental studies evaluated the effect of different agents on wound healing [2][3][4][5]21]. These agents may be pharmaceutical/medical substances as shown by certain studies.…”
Section: Discussionmentioning
confidence: 99%
“…Most skin wounds heal naturally. Various agents were applied in previous studies to accelerate wound healing and increase wound strength [2][3][4][5]. Incisional wound model is often used in experimental and clinical studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that ABS has strong antimicrobial properties along with its effectiveness in bleeding control [11]. In the studies it was suggested that ABS can be used in dental treatments because of its hemostatic activity and strong antimicrobial properties [12,13].…”
Section: Introductionmentioning
confidence: 99%